The Search for Salvation: Nazik Al-Malaika's Utopia - Rababah, Mousa (Dirasat: Human and Social Sciences, 2025)
Objectives: This paper attempts to explore Nazik Al-Malaika's personal utopia as manifested in her poem "The Lost Utopia," which represents a state of existential awareness. The poem embodies a clear stance on the interaction between the poetic self and its surroundings. Methods: The research adopts the analytical method as a basis to approach the poem and to explore how the poet depicted her utopia, transforming it into a special poetic vision. Results: An analysis of the poem reveals a fluctuation in the poet's relationship with her existence. While desolation and alienation dominate her poetry, in her utopia, she attempts to unveil a qualitative relationship with the self through her interaction with moments of optimism, hope, and dreams associated with the utopia. Hence, most sections of this article are titled to align with this vision, as follows: Creating a Utopia, The Dream Place, Utopia of Nature, Mythologizing Utopia, Utopia of Sensation, Utopia of Security, Utopia and the Horizon of Dreams, Utopia of Salvation, and Utopia as an Eternal Horizon. Conclusions: Utopia, in Nazik's poem, represents a romantic engagement with reality, which she portrays tragically, emphasizing the self's attempt to fathom the world of existence, dominated by darkness and gloom. As Nazik’s universe is often framed by pessimistic and melancholic visions, this poem becomes an expression of a different perspective, in which the poet seeks reconciliation with the self and existence, even if only in the realm of dreams.